2018
DOI: 10.1111/1751-7915.13304
|View full text |Cite
|
Sign up to set email alerts
|

Insight into metabolic diversity of the brown‐rot basidiomycete Postia placenta responsible for sesquiterpene biosynthesis: semi‐comprehensive screening of cytochrome P450 monooxygenase involved in protoilludene metabolism

Abstract: SummaryA wide variety of sesquiterpenoids have been isolated from basidiomycetes, and their bioactive properties have attracted significant attention in an effort to understand biosynthetic machineries. As both sesquiterpene synthases and cytochrome P450 monooxygenases play key roles in the diversification of sesquiterpenoids, it is important to widely and mutually understand their biochemical properties. In this study, we performed genome‐wide annotation and functional characterization of sesquiterpene syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 61 publications
8
48
0
Order By: Relevance
“…Even if a gene is expressed, alternative splice variants may be produced that are not functional (2). All pioneering work to access the large diversity of terpenoid NPs made by basidiomycetes has therefore relied on the amplification of functional terpene synthase (TS) genes from cDNA for expression and characterization in Escherichia coli or yeasts, limiting the complete functional analysis of all computationally identified TSs in basidiomycete genomes (9)(10)(11)(12)(13). Being able to directly express basidiomycete biosynthetic genes from genomic DNA in a suitable fungal surrogate host would therefore greatly accelerate the functional characterization of NP pathways.…”
mentioning
confidence: 99%
“…Even if a gene is expressed, alternative splice variants may be produced that are not functional (2). All pioneering work to access the large diversity of terpenoid NPs made by basidiomycetes has therefore relied on the amplification of functional terpene synthase (TS) genes from cDNA for expression and characterization in Escherichia coli or yeasts, limiting the complete functional analysis of all computationally identified TSs in basidiomycete genomes (9)(10)(11)(12)(13). Being able to directly express basidiomycete biosynthetic genes from genomic DNA in a suitable fungal surrogate host would therefore greatly accelerate the functional characterization of NP pathways.…”
mentioning
confidence: 99%
“…b-caryophyllene and cubenol 18 ) and monoterpenes (linalool 14 , limonene 14 and 1,8-cineole 19 ). To our knowledge, to date, there are only a couple of fungal monoterpene synthases reported in literature (Hyp3, a 1,8-cineole synthase 19 and the very recently identified PpSTS25, a bifunctional myrcene/linalool synthase 20 ). Here, we addressed this gap and specifically explored fungal linalool synthases.…”
Section: Resultsmentioning
confidence: 99%
“…(R)-linalool synthases were marked with "▲", (S)-linalool synthases with "△", LNSs with "=" and nerolidol synthases with "■". PpSTS25 is a myrcene/linalool synthase (MLS) from Postia placenta 20 . For plant and bacterial enzymes, UniProt accession number were used.…”
Section: Gc-ms Detection and Quantification Of Terpenesmentioning
confidence: 99%
“…Sesquiterpene synthases play an essential role in diversifying the skeletal structure of sesquiterpenoids by catalyzing the very complex cyclisation of the common precursor, FPP [38,70,71,72]. Sesquiterpenoids have been reported in Inonotus [43]; however, no biosynthetic genes have been identified.…”
Section: Resultsmentioning
confidence: 99%
“…The rich bouquet of several VOCs contribute to the aroma and flavor of mushrooms. Though the ecological function of fungal volatiles is unknown, studies showed their biological activities as antibiotics, antioxidants or inhibitor of germination [72,73,74].…”
Section: Resultsmentioning
confidence: 99%